2013
DOI: 10.1111/fcre.12023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the work of Australia's Family Relationship Centres: Evidence from the first 5 years

Abstract: Family Relationship Centres (FRCs) have been described as a centerpiece of Australia's 2006 family law reforms. This paper places these centres in the larger context of the reforms and their commitment to providing community‐based family services in the family law area. The paper also examines the empirical evidence regarding FRCs' use and effectiveness. It notes that while the objectives and intentions of FRCs place considerable emphasis on strengthening family relationships and assisting families to stay tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…Furthermore, ninety-five percent of clients are satisfied with the process and agreements reached at the centers are lasting. 36 The Family Law Bar can endorse the center concept and establish a goal of creating centers in every community. Lawyers can serve on governing boards and lobby appropriate bodies for necessary regulatory reform and financial support.…”
Section: Support the Creation Of Centers In Diverse Communitiesmentioning
confidence: 99%
“…Furthermore, ninety-five percent of clients are satisfied with the process and agreements reached at the centers are lasting. 36 The Family Law Bar can endorse the center concept and establish a goal of creating centers in every community. Lawyers can serve on governing boards and lobby appropriate bodies for necessary regulatory reform and financial support.…”
Section: Support the Creation Of Centers In Diverse Communitiesmentioning
confidence: 99%
“…Research in the United States and Australia has found that about two-thirds of completed family mediations result in parenting agreements, which resolve at least some of the areas of disagreement between the coparents (Kelly, 2004;Moloney, Qu, Weston, & Hand, 2013). However, a substantial minority of separated parents have ongoing conflict about parenting matters, and might benefit from more intensive help like family therapy (Lebow & Newcomb Rekart, 2007).…”
Section: Family Mediationmentioning
confidence: 99%
“…While the third goal has been clearly met, only a small percentage of cohabiting and married couples have used FRCs for the first two goals (Moloney, Qu, Weston, & Hand, 2013). The FRCs would be the first point of entry for everyone, and from that entry point all referrals and services would proceed, depending on the parents' circumstances.…”
Section: Using a Single Community-based Entry Pointmentioning
confidence: 99%
“…The majority of parents (70%) indicated that their children's needs were taken into account in the FDR process and 60% believed that the parenting agreement worked for the children and for themselves (Moloney, Qu, Weston, & Hand, 2013). Among parents attending FRCs, 49% of fathers and 44% of mothers indicated that the parenting agreement reached in the FDR process increased the amount of time that the children spent with their fathers when compared to the contact pattern prior to attending FDR, but the actual amount of parenting time for each parent does not appear to have been assessed.…”
Section: Ongoing Evaluation Of Family Relationship Centresmentioning
confidence: 99%
See 1 more Smart Citation